Fatigue properties (S–N and da/dN–ΔK) of cast aluminium alloys. (April 2013) - Okayasu, M; Takasu, S; Niikura, A; Okano, S; Shiraishi, T
Abstract : In this paper, the fatigue strengths of cast aluminium alloys have been examined using the S – N and d a /d N –Δ K approaches on various cast samples having different microstructural characteristics. These were made by several different casting techniques, namely gravity casting, die casting and twin rolled continuous casting. Owing to the different microstructures, the fatigue properties varied. The S – N relations, e.g. the endurance limit, of the twin-rolled casting were apparently high compared to the other cast samples. The high fatigue strength was related to the high tensile strength and high ductility caused by the tiny spherical α -Al phase and fine eutectic structure. On the other hand, the low fatigue strength for the gravity and die cast samples was caused by the high stress concentration caused by the α -Al phase and needle-like eutectic silicon. Unlike the fatigue strength in the S – N approach, the d a /d N –Δ K relationships for the twin rolled casting sample, i.e. the resistance to fatigue crack propagation, were low compared to the gravity casting and the die cast samples. Such a difference in the crack growth resistance was influenced by the crack growth characteristics. For example, for the gravity cast and the die cast samples, the crack growth occurs in the grain boundaries of the coarse α -Al phase and along the long eutectic silicon grains (zigzag crack path), which promotes a strong crack closure tendency, leading to high crack growth resistance. The difference in the fatigue strength determined from the S – N relation and d a /d N –Δ K relation was interpreted by experimental and numerical examination of the stress–strain distribution.